PENGARUH PROFITABILITAS, LIKUIDITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI DI BEI - Dewi, Kadek Yuliana; Rahyuda, Henny (E-Jurnal Manajemen; Vol 9 No 4 (2020)DO - 10.24843/EJMUNUD.2020.v09.i04.p02, 2020)
The purpose of this study is to determine the significance of the effect of profitability, liquidity and dividend policy on firm value. This research was conducted at the consumer goods industry sector companies on the Indonesia Stock Exchange (BEI) 2016-2018 period. The number of samples in this study were 17 companies with a purposive sampling method. Data collection was carried out using a non-participant observation method, through financial statement data published on the IDX's official website, www.idx.co.id. The results of the analysis showed that profitability had a significant positive effect on firm value. Liquidity and dividend policy have a significant negative effect on firm value. This means that profitability is the main factor that most influences the value of the company and is considered by investors to invest. Keywords: firm value, profitability, liquidity, dividend policy